A Survey for Secure Routing Protocol Used in Internet of Things (IoT) (International Journal of Innovative Research in Engineering & Management, 2022)
IoT devices are the integral part of this  century. It is estimated that more than 40 billion devices  are connected and this number is increasing exponentially  due to the heavy dependency of IoT with every field. These  devices collect their concerned data through their sensors  and allow the business to work smoothly. The routing  protocols used by these IoT devices play a vital role in  delivery of collected data packets. Routing protocols  governs several factors among which security as well as  fast delivery are the major ones. Several researchers have  proposed various routing protocols that can handle the  secure as well as efficient source to destination route for  the packets. But still due to various shortcomings in the  area of security and fast delivery of packets there is need  for better as well as more optimized routing protocol. Our  paper aims to review some of the latest research paper  published in this area so that the researchers can get to  know about the latest work in this field and carry on with  their research.
Keywords: IoT; Routing protocols; Challenges; Security